EP413 Definitive radiotherapy with low cumulative doses for uterine cervical cancer: a japanese prospective study with no midline block. (1st November 2019) - Toita, T; Kusada, T; Ariga, T; Kudaka, W; Maemoto, H; Makino, W; Ishikawa, K; Heianna, J; Nagai, Y; Aoki, Y; Murayama, S
Abstract : Introduction/Background: A midline block (MB) used in whole pelvic RT (WPRT) hinders accurate interpretation of the treatment outcome due to uncertainty of the RT dose delivered to cervical tumours. Methodology: Patients with cervical cancer of FIGO stages IB1-IVA were eligible for this prospective study. The treatment protocol consisted of WPRT (non-IMRT) without a MB (45 Gy/25 fractions) and CT-based high-dose-rate intracavitary brachytherapy (HDR-ICBT; 15 Gy/3 fractions or 20 Gy/4 fractions, prescribed to point A). The total EQD2 to point A was 63 or 69.3 Gy. The HR-CTV was contoured at the time of the present analyses. If optimisation (manual adjustment of the dwell times) was inadequate to meet the organ-at-risk dose constraints, the point A dose was decreased. Graphical optimisation was not performed. Results: A total of 40 patients were enrolled. The FIGO stage distribution was IB1, 11; IB2, 13; IIA2, 1: IIB, 11; IIIB, 3; IVA, 1. The median pretreatment tumour diameter was 47 mm (14–81 mm). No patients underwent hybrid ICBT. The point A dose was decreased in 19 of 153 ICBT sessions (12%). Twenty-nine patients received concurrent chemoradiotherapy. After a median follow-up of 33 months, the 2-year pelvic progression-free survival (PPFS), and overall survival rates were 83%, and 85%, respectively. A HR-CTV D90 threshold of 70 Gy was correlated with the PPFS: 93% for patients receiving ≥70 Gy (n=29) versus 64% for those receiving <70 Gy (n=11) (P=0.018). Late adverse events (grade ≥3) were observed in three patients (bladder in two, rectum in one). Conclusion: Definitive RT consisting of WPRT without a MB and HDR-ICBT was feasible in our cohort of Japanese patients. A low RT dose might be adequate for patients with non-bulky tumours. Proper 3D-IGBT using graphical optimisation and a suitable hybrid technique, based on appropriate HR-CTV contouring, is recommended to improve outcomes further. Disclosure: Nothing to disclose.